The Policies of Balai Pustaka as the Dutch Colonial Government’s Publishing Agency in 1917-1942 - Sulistya Putri; Dewi Yuliati; Dhanang Respati Puguh (IHiS (Indonesian Historical Studies), 2021)
The Ethical Policy (1901) generated many intellectuals who were able to express their ideas and opinion of nationalism and opposition through written media. The colonial government felt restless and needed a sensor agency for the intellectual’s works. In 1908 the colonial government started to establish the Commission for People’s Reading which in 1917 changed to Balai Pustaka. This was the Dutch Colonial Government’s first publishing agency with privileged rights in the monopoly on the publishing and printing industries. Balai Pustaka also created a policy supporting a sensor function. This study aims at analyzing the implementation of Balai Pustaka’s function as the sensor agency for literary works in ensuring the colonial government’s social-political stability in Dutch East Indies. The critical historical method of political approach was employed in this research, especially in the scope of colonialism and political policy. The policy issued by Balai Pustaka consists of three forms, namely: preproduction, production and postproduction policies. The preproduction policy was in the form of Nota Rinkes containing rules of the content of script to be issued, corporate management policy, and recruitment. Production policy covers editing (modification and hyphenation) and control over scripts received by Balai Pustaka. Meanwhile, postproduction policy was in the form of distribution of script by establishing more Taman Pustaka, expanding sales agents, and performing mobile library program. Other than these, Balai Pustaka also actively sued publication which were not published by it and by idea and notion opposing the colonial government.